The Left in the United States and the Decline of the Socialist Party of America, 1934–1935 - Zumoff, Jacob A. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
In the early years of the Great Depression, the American Socialist Party (sp) attracted left-wing youth and intellectuals at the same time that it faced the challenges of distinguishing itself from the Democratic Party of Franklin D. Roosevelt. By 1936, as its right-wing historic leadership (the “Old Guard”) left the sp and many of the more left-wing members of the sp had decamped, the party dwindled to a shell of its former strength. This article examines the internal struggles within the sp between the Old Guard and the left-wing “Militant” groupings and analyzes how the groups to the left of the sp reacted, particularly the pro-Moscow Communist Party and the supporters of Trotsky and Bukharin who were organized into two smaller groups, the Communist Party (Opposition) and Workers Party.